2005
DOI: 10.1128/iai.73.4.2306-2311.2005
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Interleukin-12 Treatment for Protection against Respiratory Infection with theFrancisella tularensisLive Vaccine Strain

Abstract: Francisella tularensis is a gram-negative intracellular bacterium that can induce lethal respiratory infection in humans and rodents. However, little is known about the role of innate or adaptive immunity in protection from respiratory tularemia. In the present study, the role of interleukin-12 (IL-12) in inducing protective immunity in the lungs against intranasal infection of mice with the live vaccine strain (LVS) of F. tularensis was investigated. It was found that gamma interferon (IFN-␥) and IL-12 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 27 publications
(23 reference statements)
8
103
2
Order By: Relevance
“…Consistent with this hypothesis, it has been shown that administration of neutralizing antibodies against tumor necrosis factor-α (TNF-α) or interferon-γ (IFN-γ) results in early death or a decrease in LD50 of mice infected with F. tularensis (8,14,17,19,24). IFN-γ null mice are also more susceptible to F. tularensis infection than their wild type counterparts (11). Treatment of macrophages with IFN-γ allows these cells to limit the growth of F. tularensis (1,2,15,22).…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…Consistent with this hypothesis, it has been shown that administration of neutralizing antibodies against tumor necrosis factor-α (TNF-α) or interferon-γ (IFN-γ) results in early death or a decrease in LD50 of mice infected with F. tularensis (8,14,17,19,24). IFN-γ null mice are also more susceptible to F. tularensis infection than their wild type counterparts (11). Treatment of macrophages with IFN-γ allows these cells to limit the growth of F. tularensis (1,2,15,22).…”
Section: Introductionsupporting
confidence: 49%
“…Survival studies were carried out using intranasal infection of mice as described by Duckett et al (11). Briefly, mice were anesthetized with ketamine and xylazine and were infected with FtB or FtMac in 40 ul of Ringer's solution containing 5,000 CFU.…”
Section: Methodsmentioning
confidence: 99%
“…novicida (9,43,45,46,51,59,79,81). IL-12 is a potent stimulus for production of IFN-γ, which in turn induces nitric oxidase synthase (iNOS) and synthesis of NO by macrophages (11,38,51,62,63).…”
Section: Cytokines and Phagocyte Activation In Host Defensementioning
confidence: 99%
“…Recent studies suggest that an inadequate innate immune response to infection with F. tularensis likely contributes to its extreme virulence in humans and mice. Indeed, proinflammatory cytokines such as TNF, IL-12, and IFN-g appear crucial for effective immunity to and survival of F. tularensis infection (3)(4)(5)(6), yet infection itself appears to attenuate or delay the expression of these critical cytokines (7)(8)(9)(10). The mechanism(s) by which F. tularensis infection delays or impairs the proinflammatory response remain unknown.…”
mentioning
confidence: 99%